2018
DOI: 10.1016/j.cobeha.2017.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and proximity in motivation and cognitive control

Abstract: Cognitive control - the ability to override a salient or prepotent action to execute a more deliberate one - is required for flexible, goal-directed behavior, and yet it is subjectively costly: decision-makers avoid allocating control resources, even when doing so affords more valuable outcomes. Dopamine likely offsets effort costs just as it does for physical effort. And yet, dopamine can also promote impulsive action, undermining control. We propose a novel hypothesis that reconciles opposing effects of dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 72 publications
(94 reference statements)
8
33
0
Order By: Relevance
“…It is consistent with previous findings that extended training makes learned responses habitual and less flexible [54,55]. Recent studies have found that dopamine activity is closely linked to initiating a movement or a sequence of learned actions [8,9,19,23,24,52,[56][57][58]. These findings, along with our simulation, suggest that during early training when an animal is uncertain about the key stimuli for the given task, many effective task dimensions-each generating a weak prediction error signal and affecting animal's behavior for a short while-guide the animal to complete the task.…”
Section: The Transition From Phasic To Ramping Patterns Upon Changes supporting
confidence: 92%
See 1 more Smart Citation
“…It is consistent with previous findings that extended training makes learned responses habitual and less flexible [54,55]. Recent studies have found that dopamine activity is closely linked to initiating a movement or a sequence of learned actions [8,9,19,23,24,52,[56][57][58]. These findings, along with our simulation, suggest that during early training when an animal is uncertain about the key stimuli for the given task, many effective task dimensions-each generating a weak prediction error signal and affecting animal's behavior for a short while-guide the animal to complete the task.…”
Section: The Transition From Phasic To Ramping Patterns Upon Changes supporting
confidence: 92%
“…Recent empirical studies have found an increasingly diverse repertoire of dopamine activity that cannot be interpreted as a prediction error signal [17,[58][59][60][61][62][63][67][68][69][70]. Our hypothesis examining the role of dopamine in resource allocation provides a framework to understand the diverse dopamine activities; prediction error is a major (but not the only) factor that determines resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous research in this area has used bandittype designs to better understand dopaminergic functions, which although useful, may not always reflect real-world problems. Furthermore, in such experiments, foreground and background reward rates can become correlated, such that the value of exploring alternatives has an instrumentally predictive value of obtaining an immediate (foreground) reward Kayser et al, 2015;Westbrook and Frank, 2018). However, in ecological settings, choices to "leave" a patch and explore are not choices between two stimuli with a predictive value but instead involve traveling to obtain rewards elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized, repeated-measures design, we also administered placebo, 45 methylphenidate (a dopamine and noradrenaline reuptake blocker), and sulpiride (a selective D2 receptor agent) while participants made explicit cost-benefit decisions about whether to engage in cognitive effort. We further monitored participants' gaze to cost and benefit attributes and assessed how fixations interacted with attribute values and dopamine to impact dynamic decision processes (8,(22)(23)(24). 50…”
mentioning
confidence: 99%